Optimal control of resources for species survival. Issue 1 (17th December 2018) - Mazari, Idriss; Nadin, Grégoire; Privat, Yannick
Abstract: Consider a species whose population density solves the steady diffusive logistic equation in a heterogeneous environment modeled with the help of a spatially non constant coefficient standing for a resources distribution in a given box. We look at maximizing the total population size with respect to resources distribution, under some biologically relevant constraints. Assuming that the diffusion rate of the species is large enough, we prove that any optimal configuration is the characteristic function of a domain standing for the resources location. Moreover, we highlight that optimal configurations look concentrated whenever the diffusion rate is large enough. In the one‐dimensional case, this problem is deeply analyzed, and for large diffusion rates, all optimal configurations are exhibited.